Les paysages de Michel Strogoff sont-ils vraiment russes ? - Laurent Touchart; Olga Motchalova; Pascal Bartout (Cybergeo, 2018)
Jules Verne wrote Michael Strogoff in 1876 for a French audience. However, since the action takes place in Russia and the geographical area is mainly Siberian, one may wonder what the Russians' attitude towards this novel was and whether they could be associated with the landscapes described. The main basis for Jules Verne’s writing was the Madame de Bourboulon’s travelogue, which translated the vision of a Franco-British woman crossing Siberia in 1861. The censorship of the Tsarist Empire prevented translation into Russian for a quarter of a century. In 1900, Fist Kiselyov’s translation largely truncated landscape descriptions and only kept those integrated into the action. A change of geographic scale leads to the study of great Siberian rivers, made with the help of a fieldwork on site and the analysis of several translations. In a general scale, Verne’s documentary readings enabled him to paint credible landscape descriptions for Russians. There are, however, some reservations which can be noticed looking at the details. The author takes some liberties with natural (incision and rapids of the Yenisei River) and urban landscapes.The views on the landscape depicted by Verne are therefore changed according to the readers, according to whether he is Siberian, Russian-European or French, and readers of different historical periods will have different opinions.